234k views
18 votes
Question below

What matrix is the result of m*H?


Enter your answer by filling in the boxes. Enter any fractions as simplified fractions.

Question below What matrix is the result of m*H? Enter your answer by filling in the-example-1
User Andy West
by
6.4k points

1 Answer

10 votes

Answer:


m * H=\left[\begin{array}{c c c}\boxed{-9} & \boxed{36} & \boxed{-(9)/(2)}\end{array}\right]

Explanation:

Calculate the value of m

Given:


3\left[\begin{array}{c c}-1 & 2 \\4 & 8\end{array}\right]=(2)/(3)m * \left[\begin{array}{c c}-1 & 2 \\4 & 8\end{array}\right]

Therefore:


\implies 3=(2)/(3)m


\implies m=3 * (3)/(2)


\implies m=(9)/(2)

Calculate the value of H

Given:


\left(H+ \left[\begin{array}{c c c}1 & 4 & -2\end{array}\right]\right)+\left[\begin{array}{c c c}3 & 2 & -6\end{array}\right]=\left[\begin{array}{c c c}-2 & 8 & -1\end{array}\right]+\left(\left[\begin{array}{c c c}1 & 4 & -2\end{array}\right]+\left[\begin{array}{c c c}3 & 2 & -6\end{array}\right]\right)

Therefore:


\implies H= \left[\begin{array}{c c c}-2 & 8 & -1\end{array}\right]

Calculating m × H


\implies m * H=(9)/(2) * \left[\begin{array}{c c c}-2 & 8 & -1\end{array}\right]


\implies m * H=\left[\begin{array}{c c c}(9)/(2)(-2) & (9)/(2)(8) & (9)/(2)(-1)\end{array}\right]


\implies m * H=\left[\begin{array}{c c c}-9 & 36 & -(9)/(2)\end{array}\right]

User Loicmathieu
by
6.4k points